Lateral torsional buckling of STEEL beams strengthened with GFRP plate. (October 2018) - Van Pham, Phe; Mohareb, Magdi; Fam, Amir
Abstract: The present study investigates the lateral-torsional buckling of wide flange steel members strengthened by a Glass Fiber Reinforced Polymer (GFRP) plate bonded to one of the flanges through an adhesive layer. A variational formulation and two finite elements are developed for the problem. The formulation captures global and local warping effects, shear deformation due to bending and twist, and partial interaction between the steel and GFRP provided by the flexible layer of adhesive. The destabilizing effects due to strong axis bending, axial force and load height effect are incorporated into the formulation. The first element involves two nodes and 16 buckling degrees of freedom (DOFs) while the second element involves three nodes and 14 DOFs. Comparisons of present model results against those based on 3D finite element analysis based on solid elements demonstrate the ability of the present models to accurately predict the buckling loads and mode shapes at a fraction of the modelling and computational efforts. Practical examples quantify the gain in elastic buckling strength achieved by GFRP strengthening, and characterize the moment gradient factors and load height effects. Elastic buckling interaction diagrams are developed for beam-columns and comparisons are provided to interaction diagrams of un-strengthened beams. Highlights: Two finite elements are developed for the buckling analysis of wide flange beam-columns strengthened with GFRP plates. The formulation accounts for global and local warping, shear deformations, and partial interaction between steel and GFRP. Predicted buckling loads and modes are in excellent agreement with 3D FEA solution. The effectiveness of the strengthening is found to be considerable for beams but negligible for columns. Moment gradient and load height recommendations are provided for the lateral torsional buckling design of beams.